PENGEMBANGAN KURIKULUM PROGRAM KHUSUS PENGEMBANGAN BAHASA ARAB BERPARADIGMA FAKULTATIF - Dr. H. Miftahul Huda, M. Ag (El-QUDWAH, 2011)
Learning Arabic is not that simply for the importance of getting language skill including istima’ skill (observing), kalam (speaking), qira’ah (reading) and kitabah (writing). But then it is for the importance of studying Islamic knowledge and even knowledge developed by faculty in UIN Maliki Malang. Up till now, curriculum in PKPBA UIN Maliki tended to have the quality subject-centered designs so it occurred discrepancy between the real need of students in that program inside of Arabic lesson. Curriculum design having facultative paradigm become one of the need to be formed in framework of establishing the purpose of developing PKPBA.Key words: curriculum design, facultative